EVALUATION OF THE PRINCIPAL'S LEADERSHIP PROGRAM IN IMPROVING PARENTS' PARTICIPATION IN CHILDREN'S EDUCATION - Binti Khoiriyah; Iis Marsithah; Mohammad Adnan (JURNAL PENDIDIKAN GLASSER, 2024)
This study aims to evaluate the principal's leadership program in improving parents' participation in children's education at SDN Inpres Biak, Luwuk Utara sub-district, Banggai district. The main issue raised was the low level of parental involvement in the children's education process, which is thought to be related to the effectiveness of the leadership program implemented by the principal. The research approach used a descriptive evaluative method with the CIPP (Context, Input, Process, Product) model. Data were collected through observations, interviews and questionnaires involving principals, teachers, parents and students. The results showed that the principal's leadership program has positively contributed to increasing parental participation through activities such as regular meetings, parenting training, and cooperation between the school and the community. However, there are still challenges in the consistency of program implementation and the low participation of some parents due to socio-economic factors. This study recommends strengthening communication between the school and parents and improving the capacity of school principals in managing leadership programs based on community participation.